The Public Institutions of Science and Technology as Knowledge Source in the Learning Networks of Agrifood Sectors in Argentina - Sanchez, Guillermo (2012)
In the case of agri‐food productions, Argentinean enterprises -mainly medium‐ and small‐sized, have a critical neck bottle that limits their possibility to build endogenous capabilities for knowledge production, circulation and appropriation. As a consequence, public institutions of science and technology have been called to play a central role in the innovation systems providing relevant inputs for the necessary learning process in order to obtain product and process innovation. Nevertheless, it looks like that these institutions, in Argentina, are prisoners of the offer (science) push?demand pull tension far away of a systemic behavior in an innovative environment. This work studies four cases of agri‐food production in Argentina, considering a regional approach and the learning networks around each production. It is concluded that the behavior of each institution is different for each case. INTA has a systemic conduct in all cases while the other ones show a systemic behavior only in the case that their offer matches to specific demands.